Criminal Accountability and Restorative Justice in Traffic Accidents that Result in the Death of the Victim (Research at the Pematangsiantar District Court) - Kaaisar Romolus Deo Sianipar; Ismaidar; Abdul Rahman Maulana Siregar (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
A traffic accident that results in the death of the victim is a legal event that causes criminal consequences for the perpetrator, especially if the incident occurred due to negligence. In law enforcement practice, the settlement of traffic accident cases is not always pursued through a repressive criminal approach, but can also be resolved through a restorative justice approach that emphasizes restoration and peace between the perpetrator and the victim's family. This study aims to analyze the form of criminal responsibility of the perpetrators of traffic accidents that resulted in the death of the victim and examine the application of restorative justice in the settlement of the case at the Pematangsiantar District Court. The results of the study show that the perpetrators of traffic accidents that resulted in the death of the victim can still be held criminally responsible based on the provisions of Article 310 paragraph (4) of Law Number 22 of 2009 concerning Road Traffic and Transportation and Article 359 of the Criminal Code.